2010
DOI: 10.1186/1477-5956-8-55
|View full text |Cite
|
Sign up to set email alerts
|

Proteome of the phytopathogen Xanthomonas citri subsp. citri: a global expression profile

Abstract: BackgroundCitrus canker is a disease caused by Xantomonas citri subsp.citri (Xac), and has emerged as one of the major threats to the worldwide citrus crop because it affects all commercial citrus varieties, decreases the production and quality of the fruits and can spread rapidly in citrus growing areas. In this work, the first proteome of Xac was analyzed using two methodologies, two-dimensional liquid chromatography (2D LC) and tandem mass spectrometry (MS/MS).ResultsIn order to gain insight into the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
1
32
0
1
Order By: Relevance
“…These proteins are secreted in response to cellular damage and protect cells by preventing accumulation of misfolded proteins and blocking apoptotic pathways [62]. Clusterin was Protein data were analyzed using the software for researching annotations of proteins (STRAP [19]). Gene ontology terms were obtained from UniProtKB and EBI GOA databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are secreted in response to cellular damage and protect cells by preventing accumulation of misfolded proteins and blocking apoptotic pathways [62]. Clusterin was Protein data were analyzed using the software for researching annotations of proteins (STRAP [19]). Gene ontology terms were obtained from UniProtKB and EBI GOA databases.…”
Section: Discussionmentioning
confidence: 99%
“…Protein identification by electrospray ionization-quadrupole-time of flight (ESI-Q-ToF) mass spectrometry: spots from the seminal plasma, cauda epididymal and seminal vesicle fluids For LC-MS/MS [19], the digested samples were injected using the nanoAcquity UPLC sample manager and the chromatographic separation was performed using a UPLC C18 column (75 μm × 10 cm) with a flow of 0.6 μL/min. The mass spectra were acquired in a Synapt G2 HDMS instrument (Waters Co., Milford, MA, USA) using a data dependent acquisition (DDA), where the three top peaks were subjected to MS/MS.…”
Section: 9mentioning
confidence: 99%
“…Proteomic studies conducted with the bacterial phytopathogen Xanthomonas axonopodis pv. citri showed that the Phenol method was employed with success [26]. In some cases, it is necessary to develop a new method due to peculiarities of the sample in question as noted by Barbarino and Lourenço in 2005 [27] due to high concentrations of salts present in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The gel-based proteomics strategies are being replaced rapidly by a new proteomics strategy based on liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) [5-8], which shows a high degree of specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%